Effective Tax Rate: Dampak Leverage, Capital Intensity Ratio Dan Kepemilikan Institusi - Deden Tarmidi; Rinaldi Okto (Universitas 17 Agustus 1945 Jakarta, 2022)
The purpose of this study is to analysis impact of leverage, capital intensity ratio, and institutional on effective tax rate. As knowed that effective tax rate is tax cost effective for entity and management as agent should know what factors can have an impact on these cost. Using mining companies listed on the Indonesia Stock Exchange in 2014-2020 as a sample, this study found a negative effect of the capital intensity ratio on the effective tax rate, while leverage and institutional ownership were not found to have a significant impact. These results explain that the high value of fixed assets has an influence on the total tax cost, with depreciation costs that can be deducted in calculating taxable income according to Article 11 of the Income Tax Law